Arabian drugs in medieval Mediterranean medicine - Amar, Zohar; Lev, Efraim (Edinburgh studies in classical Islamic history and culture, 2017)
This book explores the impact of Greek (as well as Indian and Persian) medical heritage on the evolution of Arab medicine and pharmacology, investigating it from the perspective of materia medica - a reliable indication of the contribution of this medical legacy.